Mouth breathing and dentocraniofacial changes in children: Mouth breathing dan perubahan dentokraniofasial pada anak - Adam Malik Hamudeng; Aliya Salsabila (Makassar Dental Journal PDGI Makassar, 2022)
Breathing is a vital process for the human body that occurs normally through the nose. One of the most common oral habits in children is mouth breathing. Mouthbreathing is a respiratory dysfunction that affects approximately 10-15% of the pediatric po-pulation. The etiology is multifactorial, with the most common cause is obstruction in the nasopharynx. Mouth breathing has wide-ranging consequences and involves different areas of the body, including the mouth, craniofacial development, upper and lower airway. This paper is aimed to determine the impact of mouth breathing on dentocraniofacial changes in children; using literaturestudy by collecting sources that relevant to the topic, processing data using the matrix method, and synthesizing infor-mation from journals that are used as references. It was concluded that mouth breathing habit in the children population have an impact to dentocraniofacial changes.